2020
DOI: 10.7150/jca.40866
|View full text |Cite
|
Sign up to set email alerts
|

Expression Status And Prognostic Value Of M6A-associated Genes in Gastric Cancer

Abstract: Purpose: Gastric cancer (GC) is a primary cause of cancer-associated mortality worldwide. N6-methyladenosine (m6A) is one of the most common RNA modifications that involves in the progression of numerous cancers. However, the expression status and function of m6A-related genes in gastric cancer is still not well understood. The current study is aimed to investigate the expression status and determinate prognostic value of m6A-related genes in gastric cancer. Methods: m6A-asssociated gene expression was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 45 publications
0
63
0
Order By: Relevance
“…For example, as an "eraser" in the process of m 6 A RNA methylation, FTO is highly expressed in breast, liver, and gastric cancer tissues compared to normal tissues, and is associated with poor prognosis, while FTO expression in bladder cancer tissues is lower than that in normal tissues. (31)(32)(33)(34) Interestingly, in this study, we analyzed the data of 479 LUAD patients extracted from the TCGA database and showed that the 19 m 6 A RNA methylation regulators we studied had abnormal expression in LUAD patients. Among them, the expression of FTO in cancer tissues of LUAD patients is signi cantly lower than that in normal tissues, which further validates the above viewpoint.…”
Section: Discussionmentioning
confidence: 96%
“…For example, as an "eraser" in the process of m 6 A RNA methylation, FTO is highly expressed in breast, liver, and gastric cancer tissues compared to normal tissues, and is associated with poor prognosis, while FTO expression in bladder cancer tissues is lower than that in normal tissues. (31)(32)(33)(34) Interestingly, in this study, we analyzed the data of 479 LUAD patients extracted from the TCGA database and showed that the 19 m 6 A RNA methylation regulators we studied had abnormal expression in LUAD patients. Among them, the expression of FTO in cancer tissues of LUAD patients is signi cantly lower than that in normal tissues, which further validates the above viewpoint.…”
Section: Discussionmentioning
confidence: 96%
“…As reported recently, m6A RNA methylation is not “good or bad” in the study of m6A and tumors, because it can promote or suppress cancer cells mainly by regulating the mRNA expression of related oncogenes or tumor suppressor genes [ 25 ]. The dysregulation of m6A regulators can affect cell proliferation, cell self-renewal and differentiation capacity, control of heat shock response [ 31 ], DNA damage response [ 32 ], tissue development [ 33 ], cell death, and development of multiple forms of human diseases, including cancer [ 8 , 11 , 19 , 34 , 35 ]. Emerging evidence has demonstrated that m6A RNA methylation regulators are also involved in the occurrence and development of many cancers: hepatocellular carcinoma [ 36 , 37 ], glioblastoma [ 35 ], osteosarcoma [ 38 ], colorectal cancer [ 39 ], and so on [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The m6A RNA methylation site in the nucleus can also be erased under the action of demethylases, known as “erasers,” mainly including ALKBH5 and FTO that can specifically target m6A RNA [ 8 , 13 15 ]. Subsequently, in the further processing of RNA in the nucleus and outside the nucleus, the m6A binding proteins, also known as “readers,” mainly including HNRNPC, YTHDC1, YTHDC2, YTHDF1, and YTHDF2, will bind to the m6A methylated site to perform a series of biological functions in regulating the stability, localization, transportation, translation, and degradation of target mRNAs that depended on the recognition of different kinds of “readers” [ 6 , 8 , 9 , 13 , 16 19 ]. Therefore, the methylation level of m6A and the expression level of m6A RNA methylation regulators may have important roles in the pathogenesis and clinical management of pRCC.…”
Section: Introductionmentioning
confidence: 99%
“…m 6 A modification stabilises LNCAROD, and LNCAROD expression correlates with poor prognosis and tumorigenicity in HNSCC [ 128 ]. In gastric cancer, m 6 A-associated genes were found to be dysregulated, and poor prognosis correlated with high expression of FTO and WTAP [ 129 ]. Moreover, m 6 A can modulate translation in acute myeloid leukemia [ 130 ], and in response to heat shock [ 131 ].…”
Section: Looking Ahead: Rna Modifications and The Ddr A Role For Rnamentioning
confidence: 99%